Current characteristics and early functional outcome of older stroke patients: a population-based study (Dijon Stroke Registry). (3rd October 2020) - Béjot, Yannick; Duloquin, Gauthier; Graber, Mathilde; Garnier, Lucie; Mohr, Sophie; Giroud, Maurice
Abstract: Background: the ongoing growing and ageing population is associated with an increase in older patients suffering a stroke. We aimed to assess the current profile of these patients in a population-based setting. Methods: all patients with acute stroke were prospectively identified among residents of Dijon, France, between 2013 and 2017, using a population-based registry. Characteristics and early outcome of patients were compared according to age groups. Results: 1, 288 stroke cases were recorded (median age: 81.1 years, interquartile range: 66.1–86.7, 54% women). Patients aged 75–85 years and those >85 years accounted for 27.6 and 33.9% of overall cases. Increasing age was associated with a greater prevalence of vascular risk factors, pre-existing cognitive impairment and handicap, higher initial severity, more frequent cardioembolic ischemic stroke, post-stroke pulmonary infection and delirium. Only 41% of patients aged 75–85 years and 18% of those aged >85 years had a good early recovery. Compared with patients aged <75 years, patients aged 75–85 years [adjusted odds ratio (OR) = 2.61; 95% confidence interval (CI): 1.74–3.93, P < 0.001] and those aged >85 years (adjusted OR = 7.18; 95% CI: 4.58–11.3, P < 0.001) had an increased risk of poor post-stroke functional outcome. Among survivors, the proportion of patients discharged to home was 60% in age group <75 years, compared with 49% in patients aged 75–85 years and 29% in those aged >85 years. Thirty per cent of patients >85 years old required a long-term care institution. Conclusion: the increasing burden of stroke in older people has major implications for future treatment strategies and need for dedicated care facilities.